NATION BUILDING AND THE DIALECTICS OF RELIGION AND RELIGIOSITY IN NIGERIA’S POLITICS - Clement Odiri Obagbinoko (International Studies Journal)
This paper interrogates the interface between politics and religion and the extent to which religion and religiosity has been deployed in Nigeria’s politics to engender societal cohesion within the Nigerian polity. There has been popular advocacy for the deployment of religion in Nigeria’s politics towards an organic society and for the purpose of strengthening national unity. Religion and politics are concepts that designate two different and interdependent subsystems of society. Although the concepts are separate analytically, the relationship between religion and politics is characterized by interdependence. Considering the critical role religion play in Nigeria’s politics, the paper therefore gauges the efficacy and effectiveness of religion as a formidable unifier and dependable vehicle towards national unity. In doing this, the paper acknowledges the existence of an age-long controversy which obtains in the relationship between religion and politics. This controversy derives from two perspectives: 1. That religion in politics may get religion desecrated or contaminated and 2. That religion in politics may not serve as a debilitating factor to politics in Nigeria but rather would serve as a purifier of our very depraved politics.